2018
DOI: 10.1093/mnras/sty2630
|View full text |Cite
|
Sign up to set email alerts
|

Celestial mechanics and polarization optics of the Kordylewski dust cloud in the Earth–Moon Lagrange point L5 – Part II. Imaging polarimetric observation: new evidence for the existence of Kordylewski dust cloud

Abstract: Telescopes mounted with polarizers can study the neutral points of the Earths atmosphere, the solar corona, the surface of planets/moons of the Solar System, distant stars, galaxies and nebulae. These examples demonstrate well that polarimetry is a useful technique to gather astronomical information from spatially extended phenomena. There are two enigmatic celestial objects that can also effectively be studied with imaging polarimetry, namely the Kordylewski dust clouds (KDCs) positioned around the L4 and L5 … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(10 citation statements)
references
References 36 publications
(67 reference statements)
0
10
0
Order By: Relevance
“…In 1989, the clouds were again photographed by Winiarski [13]. On the other hand, many scholars are strongly skeptical about the existence of the KDCs (Roosen, Harrington & Jeffreys 1967; Bruman 1969; Valdes & Freitas 1983; Igenbergs et al 2012) [14]. According to these scholars, the KDCs cannot exist around the EML4 and EML5 points for long due to the gravitational perturbation from the Sun, solar wind, and other planets [14].…”
Section: Current Observation Status Of the Kdcsmentioning
confidence: 99%
See 2 more Smart Citations
“…In 1989, the clouds were again photographed by Winiarski [13]. On the other hand, many scholars are strongly skeptical about the existence of the KDCs (Roosen, Harrington & Jeffreys 1967; Bruman 1969; Valdes & Freitas 1983; Igenbergs et al 2012) [14]. According to these scholars, the KDCs cannot exist around the EML4 and EML5 points for long due to the gravitational perturbation from the Sun, solar wind, and other planets [14].…”
Section: Current Observation Status Of the Kdcsmentioning
confidence: 99%
“…Although the KDCs cannot exist for a long time, they still have the chance of short-term survival. From June to October in 2017, Slíz-Balogh et al [14] made successful observations by using ground-based polarized light photography technology. Through a series of innovative methods, the important indirect evidence of dynamic stability of the KDCs is 3 Space: Science & Technology obtained [14].…”
Section: Current Observation Status Of the Kdcsmentioning
confidence: 99%
See 1 more Smart Citation
“…These so called Kordylewski dust clouds are so faint that proving their existence has been rather difficult. Slíz-Balogh et al (2018) concluded -on the basis of polarimetric observations-that they do exist despite the Japanese Hiten space probe not finding an increase in the concentration of dust compared to the surrounding space when passing through the Earth-Moon L4 and L5 points (Igenbergs et al 1991).…”
Section: Trojan Populations In the Solar Systemmentioning
confidence: 99%
“…Due to reflecting the rich spectral and spatial characteristics, hyperspectral imaging is widely used in agricultural detection [ 1 , 2 ], food production [ 3 , 4 ], biomedical identification [ 5 , 6 ] and other fields. Polarization imaging plays an indispensable role in environmental monitoring [ 7 , 8 ], astronomical observation [ 9 , 10 ], tumorigenesis detection [ 11 , 12 ] and other aspects. Meanwhile, polarization hyperspectral imaging naturally shows multiple applications in non-destructive quality evaluation [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%